Antioxidant Enzymes in Serum of Patients with Painful Acute Periradicular Abscess - Sinan Evcil, Mehmet; Uzun, Ismail; Demircan, Berna; Keles, Ali (Asian Journal of Chemistry, 2010)
The purpose of this study was to compare the pre-treatment and post-treatment serum antioxidants levels in acute periradicular abscess, with pain. Thirty-two patients (18 males, 14 females) with acute and painful endodontic abscesses were included in this study. Before treatment, patients had severe symptoms of inflammation, but at the end of treatment no symptoms of inflammation were observed. Glutathione reductase and catalase activities concentrations were measured in serum of patients with acute periradicular abscess, before and after treatment. There was no statistically significant effect on levels of catalase activity and glutathione reductase concentrations (p > 0.05).